2009
DOI: 10.1080/13682820701778135
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of speech‐pathology and audiology students concerning death and dying: a preliminary study

Abstract: Education in death and dying is needed by pre-professional, speech-language pathology and audiology students who appear to be at risk for professional obstacles and emotional trauma from the death of their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Given the high emotional demands of such work, and the drastic consequences of mismanagement, it is unsurprising that SLTs and other professionals are more open and personable with their patients, perhaps to compensate for feelings of powerlessness around patient outcomes. In light of this, it is important that palliative care staff receive sufficient support and bespoke training to support them with these difficult emotional aspects of their role, as well as training in dealing with death and dying for students prior to starting clinical work (Rivers, Perkins & Carson, 2009). SLTs, and other professionals working in palliative care, are required to be comfortable with talking openly about death and dying, and preparing patients and significant others for the end of life.…”
Section: Dealing With Lossmentioning
confidence: 99%
“…Given the high emotional demands of such work, and the drastic consequences of mismanagement, it is unsurprising that SLTs and other professionals are more open and personable with their patients, perhaps to compensate for feelings of powerlessness around patient outcomes. In light of this, it is important that palliative care staff receive sufficient support and bespoke training to support them with these difficult emotional aspects of their role, as well as training in dealing with death and dying for students prior to starting clinical work (Rivers, Perkins & Carson, 2009). SLTs, and other professionals working in palliative care, are required to be comfortable with talking openly about death and dying, and preparing patients and significant others for the end of life.…”
Section: Dealing With Lossmentioning
confidence: 99%
“…On the contrary, it has been suggested that medical and allied health professionals who are not prepared for work in palliative care are at an increased risk of negative consequences such as stress, anxiety and burnout (Rivers et al . , Truffelli et al . , Meier et al .…”
Section: Introductionmentioning
confidence: 99%
“…Education at the university level results in several positive outcomes for students, such as improved competence (Bush and Shahwan-Akl 2013), better attitudes (Anderson et al 2008, Kumar et al 2011, increased self-awareness and personal development (Ballesteros et al 2014), and improved knowledge (Kumar et al 2011, Anderson et al 2008, Ballesteros et al 2014 in relation to palliative care. On the contrary, it has been suggested that medical and allied health professionals who are not prepared for work in palliative care are at an increased risk of negative consequences such as stress, anxiety and burnout (Rivers et al 2009, Truffelli et al 2008, Meier et al 2001. Mathisen et al (2010) investigated the incorporation of palliative care units (via the Palliative Care Curriculum for Undergraduates (PCC4U) programme) into their undergraduate speech pathology curriculum at The University of Newcastle.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, speech-language pathology and audiology students indicated that they felt such training would be beneficial but preferred to gain the information through experience or by consulting professional resources rather than additional coursework (Rivers, Perkins, & Carson, 2009). Few communication disorders programs offer specific coursework designed to prepare their graduates for dealing with the death of their patients.…”
Section: Topics In Language Disorders/april-june 2012mentioning
confidence: 99%